Streptomyces salinarius sp. nov., an actinomycete isolated from solar saltern soil - Khanungkan Klanbut; Thitiya Rattanakavil; Thitikorn Duangupama; Chanwit Suriyachadkun; Paul Herron; Chitti Thawai (INTERNATIONAL JOURNAL OF SYSTEMATIC AND EVOLUTIONARY MICROBIOLOGY, 2023)
).
Keywords: Genomics and Phylogenetic Studies; Microbial Community Ecology and Physiology; Actinomycetales infections and treatment